2013
DOI: 10.3109/09286586.2012.742552
|View full text |Cite
|
Sign up to set email alerts
|

Optic Neuropathy among a Prison Population in Papua New Guinea

Abstract: A cluster of ON associated with folate deficiency has been identified. Recommendations for dietary change and micronutrient supplementation have been made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
(43 reference statements)
0
8
0
1
Order By: Relevance
“…On the other hand, the high prevalence of underweight among the convicts could be due to low rations and quality of food served on top of severe prison related stress [50, 51]. Previous studies have also reported that prisoners faced a wide spectrum of nutritional problems [1012, 14, 41, 52–54] and diets were not balanced [13, 54]. Nevertheless, it is important to note that our observed burden of underweight among the prisoners could be overestimated due to the fact that our study was based on prisoners who had respiratory/TB infection in which weight loss is a typical feature of such health problems.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the high prevalence of underweight among the convicts could be due to low rations and quality of food served on top of severe prison related stress [50, 51]. Previous studies have also reported that prisoners faced a wide spectrum of nutritional problems [1012, 14, 41, 52–54] and diets were not balanced [13, 54]. Nevertheless, it is important to note that our observed burden of underweight among the prisoners could be overestimated due to the fact that our study was based on prisoners who had respiratory/TB infection in which weight loss is a typical feature of such health problems.…”
Section: Discussionmentioning
confidence: 99%
“…Xerophthalmia in the prisoners was found to be associated with a low intake of vitamin A [8] and optic neuropathy with low folate status [7]. The extremely low folate concentrations found would render the prisoners at high risk of megaloblastic anaemia [30].…”
Section: Discussionmentioning
confidence: 99%
“…In response to the report, and in order to provide evidence-based advice to prison authorities, an ophthalmic and nutritional survey was undertaken to identify the prevalence of optic neuropathy and to investigate potential nutritional and toxic correlates of the disease. As a result of this investigation, optic neuropathy with a prevalence estimate of 10.4% among prisoners was found to be associated with length of incarceration, age, and low blood folate concentrations [7]. Some prisoners exhibited xerophthalmia associated with vitamin A deficiency [8].…”
Section: Introductionmentioning
confidence: 99%
“…With folate replacement therapy, their vision improved within 4-12 weeks of symptom onset. A recent report of optic neuropathy among prisoners in Papua New Guinea was also linked to isolated folate defi ciency [ 33 ].…”
Section: Folic Acid Defi Ciency Optic Neuropathymentioning
confidence: 98%